Liver specific expression of Cu/ZnSOD extends the lifespan of Sod1 null mice - Zhang, Yiqiang (Mech Ageing Dev, 2016)
Genetic ablation of CuZn-superoxide dismutase (Sod1) in mice (Sod1(−/−) mice) leads to shortened lifespan with a dramatic increase in hepatocellular carcinoma and accelerated aging phenotypes, including early onset sarcopenia. To study the tissue specific effects of oxidative stress in the Sod1(−/−) mice, we generated mice that only express the human SOD1 gene specifically in the liver of Sod1(−/−) mice (Sod1(−/−)/hSOD1(alb) mice). Expression of hSOD1 in the liver of Sod1(−/−) mice improved liver function, reduced oxidative damage in liver, and partially restored the expression of several genes involved in tumorigenesis, which are abnormally expressed in the livers of the Sod1(−/−) mice. However, liver specific expression of hSOD1 did not prevent the loss of body weight and muscle mass and alterations in the structure of neuromuscular junctions. The expression of hSOD1 in the liver of Sod1(−/−) mice significantly improved the lifespan of Sod1(−/−) mice; however, the lifespan of the Sod1(−/−)/hSOD1(alb) mice was still significantly shorter than wild type mice.